Effectiveness of Education Program on Secondary Schools Students Knowledge about Dysmenorrhea in Alnasiriya City Schools - Riyadh, Asala; Hikmat, Suhad (Iraqi National Journal of Nursing Specialties, 2018)
Abstract:Objective: The study aim is to assess knowledge of secondary schools female students regarding dysmenorrhea; find out the effectiveness of education program on secondary schools students and also to identify relationship between education program and certain variables.Methodology: The quasi-experimental design (pretest and posttest) on one hundred students 4th year in Khawla Bint Al-Azwar secondary school for females at morning shift in Al Nasiriya City, data collection started at 4th March to 18th March 2018. A non-probability (purposive) sample of (100) students (50) student from scientific branch and (50) students from literary branch. Data have been collected through using a questionnaire modeled and made up of three parts; the first part includes demographic data of study sample; the second part includes the previous history of students' menstrual cycle; and the third part includes the collection dysmenorrhea knowledge program, a study samples filled by the female students themselves concerning their dysmenorrhea knowledge program. Data were collected through three stages pretest stage; educational program stage and posttest stage. Validity is determined through a panel of 14 experts, and the reliability of the questionnaire is determined through pilot study of (15) students chosen randomly. Data ate analyzed through descriptive inferential procedure.Results: The present study concludes that health education session can improve students' knowledge and raise their awareness regarding dysmenorrhea, in addition the statistical test shows that the student's age and the parents educational level have positive statistical association with educational program.Recommendations: The study recommends that the Ministry of Health need to: design education program that focus on parents, school teachers and administrative board to address the menstrual disorders also, school nurse help the student to cope with dysmenorrhea since the condition can limit student school performance.Ministry of Education needs to set education program that can change student life style through regular physical exercise classes and mass media.